AFIKSASI BAHASA DAYAK BAKATI DIALEK RARA DUSUN PIJU DESA SELUAS KABUPATEN BENGKAYANG - Evsan Koni; Laurensius Salem; Nanang Heryana (Universitas Tanjungpura, 2020)
AbstractThe Rara dialect Dayak language hereinafter abbreviated (BDBDR) is one of the regional languages in Bengkayang Regency. Speakers of this language are spread around Seluas Dusun Piju, Bengkayang Regency. This research was motivated by: (1) BDBDR language is used in formal and non-formal situations, namely as a means of communication between speakers of the Dayak Bakati Rara dialect community, (2) BDBDR is a verbal variety that is very easy to change due to the influence of other languages. (3) the writer wants to describe BDBDR to other speakers. The general problem that will be discussed in this study is how the affixation of the Rara dialect of Dayak Bakati is limited to three sub-problems, namely: form, function and meaning. The purpose of this study is to describe the form, function and meaning of the Dayak Bakati Rara dialect. This research uses a descriptive method. This form of research is qualitative. The data source in this study is BDBDR spoken by the Dayak Bakati Rara dialect in the Piju hamlet of Seluas sub-district. The data in this study are affixes of the Rara dialect of Dayak Bakati which are contained in words spoken by the Dayak Bakati community in the Piju hamlet of Seluas sub-district. The techniques used in the research are: skillful looking techniques, image show techniques, interview techniques and documentary studies. The tools used in this study are the researchers themselves, recording devices, pictures, folklore, song lyrics of the Dayak Bakati language in the Rara dialect.Keywords: Dayak Bakati language, affix, Rara Dialect